Pension reforms : key issues illustrated with an actuarial model - Oksanen, Heikki; European Commission : Directorate-General for Economic and Financial Affairs (Brussels ; Belgium : European Commission: Directorate-General for Economic and Financial Affairs, 2004)
The paper examines pension reform under ageing. Using stylised facts, ageing is traced to low fertility and increasing longevity. Given these persistent factors, pension systems must be reformed to avoid an unfair burden being left for future generations.
Economic Papers